The Effect of Project-Based Learning and Recitation Models on the Ability of Prospective Teachers to Develop Teaching Modules Islamic Religious Education - Muhammad Idris; Amrullah; Sutarto; Ahmad Darlis (LPPM Universitas Ibn Khaldun, Bogor, 2025)
This study aims to analyze students' ability to develop teaching modules using the Project-Based Learning (PjBL) and Recitation models. This study uses a non-experimental correlational quantitative method, which aims to identify and describe data related to the research variables. A sampling technique was used with 40 respondents. Data were obtained and analyzed using descriptive statistics, normality tests, and ANOVA. The results of the study determined that the average ability of students in developing teaching modules was 60.35 with a standard deviation of 7.614. The normality test showed that the data were normally distributed with a Skewness value of 0.020 and Kurtosis of -0.775. The ANOVA test yielded a significance value of <0.001, indicating that the PjBL and Recitation variables significantly influence students' ability to develop instructional modules. The coefficient of determination (R Square) of 0.439 indicates that the independent variables together explain 43.9% of the variation in the dependent variable, i.e., the ability to develop instructional modules, with the remaining 56.1% influenced by other factors.